Memory or acclimation of water stress in pea rely on root system's plasticity and plant's ionome modulation - Jacques, Cécile; Girodet, Sylvie; Leroy, Fanny; Pluchon, Sylvain; Salon, Christophe; Prudent, Marion (Frontiers in Plant Science, 2023)
Introduction Peas, as legume crops, could play a major role in the future of food security in the context of worldwide human nutrient deficiencies coupled with the growing need to reduce consumption of animal products. However, pea yields, in terms of quantity and quality (i.e. grain content), are both susceptible to climate change, and more specifically to water deficits, which nowadays occur more frequently during crop growth cycles and tend to last longer. The impact of soil water stress on plant development and plant growth is complex, as its impact varies depending on soil water availability (through the modulation of elements available in the soil), and by the plant’s ability to acclimate to continuous stress or to memorize previous stress events. Method To identify the strategies underlying these plant responses to water stress events, pea plants were grown in controlled conditions under optimal water treatment and different types of water stress; transient (during vegetative or reproductive periods), recurrent, and continuous (throughout the plant growth cycle). Traits related to water, carbon, and ionome uptake and uses were measured and allowed the identification typical plant strategies to cope with water stress. Conclusion Our results highlighted (i) the common responses to the three types of water stress in shoots, involving manganese (Mn) in particular, (ii) the potential implications of boron (B) for root architecture modification under continuous stress, and (iii) the establishment of an “ecophysiological imprint” in the root system via an increase in nodule numbers during the recovery period.